Between Education and Marketing: A Semiotic Analysis of Skincare Advertising on TikTok and Instagram - Mohammad Nico Fitriyanto; Farida Nurul Rahmawati; Agus Ferdianto; Aufi Akmil Imami (Yayasan Citra Dharma Cindekia, 2026)
Social media has intensified the circulation of skincare messages that combine health education with product promotion. This study examines how skincare advertising content on TikTok and Instagram constructs meanings of education and marketing through visual, verbal, and audiovisual signs. The study applies a qualitative semiotic approach based on Charles Sanders Peirce's triadic model of sign, object, and interpretant. The research objects are skincare-related advertising and review contents from Instagram @skincarewanita.id and TikTok @hallo.manis, selected purposively because they display product comparison, recommendation, and educational claims. Data were collected through content observation, screenshot documentation, caption analysis, and audience-comment reading. The results show that Instagram tends to construct skincare messages through static visual comparison, carousel narratives, product labels, and concise claim texts, whereas TikTok builds persuasion through creator performance, spoken testimony, trending audio, facial expression, and fast-paced editing. Both platforms use educational signs such as ingredient explanations, skin-type categories, and usage tips; however, these signs often operate simultaneously as promotional cues that direct audiences toward particular products. The study concludes that the meaning of skincare education in social media advertising is not neutral, because it is shaped by persuasive commercial codes, influencer credibility, and platform-specific forms of attention.